Language Studies of The Qur'an (Arabic Language Style in Makkiyah and Madaniyah Verses) - La Ode Muh. Nanang Pribadi Rere (International Journal of Religion, Humanity and Cultural Heritage, 2025)
Language cannot be removed from a culture in human generations. Arab society before Islam was born was known as a society that was good at poetry. The area called Ukaz became a place for poetry competitions for the Arab community at that time. The Qur'an as the holy book of Muslims is present in the midst of a society that has good abilities in poetry, so it must have a better and stronger language structure. This is because the Qur'an is the word of Allah SWT. Therefore, it is very important to study the structure of language. This article examines the structure of Arabic language in the verses of the Qur'an. To organize and complete the argument of the author, in this article the author quotes various opinions from experts in the field of ulumul Qur'an who study the language of the Qur'an. From the results of the study that the author documents in this article, it shows that the Qur'an has an extensive language style and also has differences with everyday language.